PENATALAKSANAAN FISIOTERAPI PADA KONDISI OARTA INSUFISIENSI NYHA II - Santi Dwi Kurniasari; Irine Dwitasari Wulandasari; Dinti Mustaqimah (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
Aortic insufficiency is a condition where the valve can not close completely so that when blood flow to part of diastole the left ventricle. Total amount of blood flow was 50 cc of the contents of sekuncup. Thus if the contents sekuncup 70 cc and 30 cc flowing again, the circulation remained normal for the ventricle must pump 100 cc of blood (70 cc to 30 cc circulation is flowing again). So the left ventricle has to work more normally resulting  in dilatation and hypertrophy.  This resulted  in shortness of  breath,  decreased activity or limited activity,  heavy dependence in performing everyday  activities,  to provide effective and efficient handling,  then conducted an examination method of examination shortness of  breath with Exertion scale,  the  noise  with auscultation.  Things that  can help to reduce the problems  mentioned  above can  be  done by the  method of Breathing Exercise, exercise therapy, early mobilization.  The  purpose of these modalities is to reduce shortness of breath, prevent the complications of bed rest is pneumonia, improving the ability of heart function and increase the tolerance ability of functional activity and restore the  function  of physiological, psychosocial,  work and get back to optimal can tolerate daily activities.